The role of competencies in foreign language education (Journal of Educational Sciences, 2021)
The article discusses one of the main directions of foreign language education - the competence-based approach, and also describes the role and purpose of competencies in foreign language education. When learning a foreign language based on the competence of intercultural communication, students should be able to compare their country with the world of the country in which the language is being studied, think about how the country differs from its own country, its mentality and attractiveness. Therefore, without knowing and not mastering the culture of the country in which the language is studied, it is impossible to achieve the level of proficiency in this language. In the modern educational paradigm, the competence-based approach is considered as a priority methodological basis for the development of goals, objectives and content of professional training of future specialists. In this regard, an analysis of the current state educational documents, as well as an analysis of the improving education system, is presented. The article clarifies the semantic features of the words "competence" and "competency". It is also emphasized that foreign linguistics can form not only communicatiion qualities, but also interactive and informational qualities, which is an objective reality in the post-industrial and information society. According to a certain field of activity, different types of competences can be designed.Key words: competence, competent, education, foreign language education, role, abilities, Intercultural communication